2002
DOI: 10.2320/matertrans.43.1403
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substrate Bias Voltage on the Properties of Cu Thin Films by Sputter Type Ion Beam Deposition

Abstract: Cu thin films have been deposited on Si (100) substrate by using a non-mass-separated ion beam deposition (IBD) system. The effect of the substrate bias voltage on the properties of the deposited films was investigated using X-ray diffraction, resistivity measurement and field emission scanning electron microscopy. In the case of Cu thin films deposited without bias voltage, a columnar structure and small grains were observed distinctly, and the electrical resistivity of the deposited Cu films was very high. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…All three methods present some drawbacks (diffuse white light does not provide a value for the thickness and relies on visual checking of the surface colour, ellipsometry relies on a guess model and Rhodin's method depends on an accurate estimation of the effective area of the resulting oxide) and it is difficult to tell which of the three is more reliable. The difference observed could also be the result of environmental factors such as the presence of impurities or different sample preparations, which have been shown to lead to different resulting metal oxides 275,276 which makes oxidizing metals very challenging to study.…”
Section: Long-term Copper Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…All three methods present some drawbacks (diffuse white light does not provide a value for the thickness and relies on visual checking of the surface colour, ellipsometry relies on a guess model and Rhodin's method depends on an accurate estimation of the effective area of the resulting oxide) and it is difficult to tell which of the three is more reliable. The difference observed could also be the result of environmental factors such as the presence of impurities or different sample preparations, which have been shown to lead to different resulting metal oxides 275,276 which makes oxidizing metals very challenging to study.…”
Section: Long-term Copper Oxidationmentioning
confidence: 99%
“…Indeed, the formation of a ∼ 2.0 − 5.0 Cu 2 O layer first, followed by a ∼ 0.9 − 1.3 CuO overlayer has been reported 3,4,291,292 . However, Lim et al 276 showed that the texture and microstructure of a thin copper film have a direct influence on the oxidation products. When oxidising a sample with a columnar structure and small grains the Cu 2 O/CuO bylayer was obtained, when oxidising a uniform sample with no obvious columnar structure and grain boundaries the cuprous oxide layer only was observed and oxidation was slower.…”
Section: Native Oxidation Of Copper In Ambient Conditionsmentioning
confidence: 99%
“…[1][2][3] Thin films of Cu are deposited by various techniques such as evaporation, sputtering, chemical vapor deposition, electroplating, and ion beam deposition. [4][5][6][7][8][9][10][11] Among these techniques, direct current (DC) magnetron sputtering is one of the best methods for practical preparation of Cu films. Since DC magnetron sputtering technique has the advantage of much better productivity than other deposition methods, it is widely used as mass production processes.…”
Section: Introductionmentioning
confidence: 99%
“…14,15) In order to investigate copper agglomeration with annealing time, the Cu/Ta/Si structure was annealed for 1 to 60 min at 650 C in H 2 atmosphere. Resistivity measurement of annealed samples was carried out with Van der Pauw method.…”
Section: Methodsmentioning
confidence: 99%